2017
DOI: 10.1186/s12931-016-0500-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological investigation on the anti-oxidant and anti-inflammatory activity of N-acetylcysteine in an ex vivo model of COPD exacerbation

Abstract: BackgroundOxidative stress is recognized to be one of predisposing factor in the pathogenesis of COPD. The oxidant/antioxidant imbalance is significantly pronounced in patients with COPD exacerbation. N-acetylcysteine (NAC) seems to be able to reduce COPD exacerbations by modulating the oxidative stress in addition to its well-known mucolytic activity, but there are discordant findings on the actual anti-oxidant activity of NAC.MethodsThe anti-oxidant effect of NAC and its impact on the inflammatory response h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 42 publications
4
53
0
1
Order By: Relevance
“…Conversely, the overnight challenge with LPS at higher concentrations (100 ng/ml) inhibited the bronchial contractility in response to medium-high EFS frequencies. The bronchial desensitization of equine airways induced by high concentrations of LPS confirms the results of our recent investigations carried out using human airways where we have demonstrated that the overnight treatment of human isolated bronchi with LPS administered at 100 ng/ml significantly inhibited the contractile tone in response to EFS [20].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Conversely, the overnight challenge with LPS at higher concentrations (100 ng/ml) inhibited the bronchial contractility in response to medium-high EFS frequencies. The bronchial desensitization of equine airways induced by high concentrations of LPS confirms the results of our recent investigations carried out using human airways where we have demonstrated that the overnight treatment of human isolated bronchi with LPS administered at 100 ng/ml significantly inhibited the contractile tone in response to EFS [20].…”
Section: Discussionsupporting
confidence: 89%
“…The day after these treatments, equine bronchial rings were mounted into the isolated organ bath system and connected to the isometric force transducers for recording the contractile response of airway smooth muscle (ASM) in response to EFS as previously described [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several neurotransmitters are released by transmural stimulation, the most representative is acetylcholine released by myelinated fibers, whereas nonmyelinated fibers mainly sustain neurogenic airway inflammation (Belvisi, ; Calzetta, Luongo, et al., ; Yu, Wang, & Robinson, ). Higher vagal frequencies activate primarily large myelinated A‐fibers, medium vagal frequencies stimulate small myelinated B‐fibers, and lower vagal frequencies induce the activation of nonmyelinated C‐fibres (Calzetta, Cazzola, et al., ; Calzetta, Luongo, et al., ; Calzetta, Rogliani, Cavalli, et al., ; Calzetta, Rogliani, Facciolo, et al., ; Calzetta, Rogliani, Mattei et al., ; Cazzola, Calzetta, Facciolo, Rogliani, & Matera, ). Therefore in this study we have stimulated equine airways by using different EFS frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent research provides the suggestion for an alternative interpretation of the cause leading to EFS hyporesponsiveness. In fact, it has been demonstrated that overnight incubation of bronchial tissue with lipopolysaccharide (LPS) may lead to desensitization of isolated airways, leading to a significant hyporesponsiveness to transmural stimulation (Cazzola et al., ). As LPS has a relevant role in the development and progression of severe equine asthma (Beeler‐Marfisi et al., ; Nevalainen et al., ; Pirie, Collie, Dixon, & McGorum, ; Pirie, Dixon, Collie, & McGorum, ; Simonen‐Jokinen, Pirie, McGorum, & Maisi, ), we cannot exclude that the bronchi used by LeBlanc et al.…”
Section: Discussionmentioning
confidence: 99%